Implementación de prototipo para telemedicina orientada a la asistencia médica de emergencia mediante tecnología Hololens - Rivera Cabrera, Erick Nicolás (2019)
The following project covers the stages of design, implementation and testing of a telemedicine prototype aimed for emergency medical assistance, using Microsoft Mixed Reality device called Hololens. The objective of this project is to provide support to health professionals in emergency situations and/or consultations in which there is no specialized staff that serves the needs of patients immediately, in remote or difficult access localizations. In first place, several terms will be explained, such as: Telemedicine, Virtual Reality, Augmented Reality, Mixed Reality, and all the fields of application that currently exist will be explained. Also, it will be detailed the levels of health care in Ecuador and define the level of biggest impact. Later, the procedures and guidelines on how to treat the patient in certain emergency situations will be explained, which will be shown in the application that will be developed for the device used; this will be tested in the Clinical Simulation Center of the Faculty of Health Sciences of UDLA, thus demonstrating the usefulness of the device both, in the application and in the real time support that the treating health professional receives from the specialist. This project can be used as a reference for future research aimed at expanding the capacity and usefulness of these technologies currently available in the health field.